Situating environmental design in the studio: an ecological learning approach - Martinez, Ricardo A. (2011)
This work explores the problem of implementation of environmental design in architectural training. This problem has been identified as a disconnection between the delivery of information by lecturing, and the application of that information in the studio. The essential nature of students in that view is passive, and their task is to correctly apply information developed by others. This work pursues the idea that 'environmental knowledge' can be grown from within the conversational nature of the design process based on the active nature of the student. The main contribution is the proposal of an ecological approach to learning, in which the whole person of the learner is deeply engaged with his learning environment. The present understanding has been informed mainly by the ecological approach to perception of James Gibson, and the conception of design of Donald Schon. Through the view of Donald Schon, environmental design comes forth as a particular instance of 'conversations' with environmental situations, involving the modeling of actual phenomena, as a central element of the learning process. Seen from an ecological approach to learning, the implementation of those 'conversations' appears as part of a larger orchestration of affordances of the learning environment, involving tangible and intangible resources. This proposal is intended to illuminate other implementation strategies of environmental design in other schools.